Kualitas Pelayanan Kesehatan Rawat Inap Di Puskesmas Mamajang Kota Makassar - Aripa, Lusyana (Barongko: Jurnal Ilmu Kesehatan, 2025)
The quality of health services is a community or individual health need based on standards that have been set by utilizing resources fairly, efficiently, and effectively within the limitations of government and community capacity, and is carried out safely and satisfactorily according to good norms and ethics. Based on the profile of Mamajang Health Center, the number of inpatients in 2017 was 51,155. Then, it increased to 56,013 in 2018. This study aimed to find out the quality of inpatient health services at Mamajang Health Center in 2020. The type of this study was qualitative using a descriptive approach. The employed data collection method was an in-depth interview. The number of informants in this study was 5 people selected by using a purposive sampling technique. Results: 1) In terms of tangibility, facilities and infrastructure for the inpatient room at Mamajang Health Center were inadequate. 2) In terms of reliability, inpatient health services at Mamajang Health Center had been accurate. 3) In terms of responsiveness, health workers had not been effective in responding to patient complaints. However, they were always ready and efficient in helping patients. 4) In terms of assurance, health workers had been trusted in providing information. However, the recovery from the disease depends on the accuracy of the medical prescription. 5) In terms of empathy, health workers had a concern for patients. Therefore, it can be concluded that the quality of services at Mamajang Health Center, Makassar has not been maximal in providing services to inpatients.